The medical student of the future: redefining competencies in a transformative era - Miguez-Pinto, João P.; Garcia-Rosa, Beatriz; Maggitti-Bezerril, Mateus; Ramalho, Clara; Garcia, Stefania L.; Pustilnik, Hugo N.; Boczar, Daniel; Avena, Katia M.; Andrade, Bruno B. (Frontiers in Medicine, 2025)
Medical education is undergoing a profound transformation, driven by rapid technological advances, evolving pedagogical strategies, and the shifting demands of healthcare systems globally. This article explores the historical evolution of medical student competencies, evaluates the current state of medical education, and envisions the future competencies required for medical school entrants and graduates. We propose a forward-looking framework for reimagining the medical student of the future, emphasizing the integration of advanced technological literacy, humanistic values, and a global perspective. By redefining these competencies, medical schools can ensure the development of adaptable, empathetic, and innovation-driven physicians for a dynamic healthcare landscape.